A scientometric analysis of global research on gut microbiota and glioma - Chen, Lize; Shu, Kun; Zhang, Zhiyin; Zhao, Jiao (Frontiers in Oncology, 2025)
BackgroundMost previous studies have demonstrated that gut microbiota is closely related to the prognosis of glioma. However, there is currently no corresponding bibliometric analysis to systematically review, analyze, and visualize prior research.Materials & methodsThis study focused on 127 publications obtained from the Web of Science Core Collection and conducted correlation analyses of authors, journals, institutions, countries, keywords, and citations using VOSviewer, CiteSpace, and the R package. ResultsThe results indicate that China and the United States are the leading countries conducting research in this field. The Anderson Cancer Center at the University of Texas in the United States and Central South University in China are the primary research institutions. DiscussionRecent studies suggest that the regulation of the brain-gut axis between gut microbiota and glioma remains a prominent research hotspot, while the anti-cancer mechanisms of the enteric nervous system and gut microbiota have emerged as significant topics in recent years. Furthermore, the receptor tyrosine kinase pathway is expected to provide extensive research opportunities in the future. This article systematically reviews the current research status and hotspots of gut microbiota in glioma for the first time, conducts a visual analysis, and explores research trends and future directions.